The function of academic manusripts in forming regional regulations in Indonesia - Dita Ayudia Pratiwi (PT WIM Solusi Prima, 2026)
This study aims 1) to determine the function of academic papers in the formation of Legislation; 2) to analyze and criticize the urgency of drafting academic texts in the formation of Regional Regulations. This type of research is normative juridical research with three approaches, namely the statutory approach, the conceptual approach and the historical approach. The results showed that the Law on the Establishment of Legislation does not clearly and in detail the regulation and function of academic papers. Even though the preparation of an academic text is an obligation in submitting a Draft Regional Regulation as mandated by Article 43 paragraph (3) of the Law on the Formation of Laws and Regulations, which confirms that the Draft Law originating from the DPR, President or DPD must be accompanied by an academic text and accompanied by an explanation or description and / or academic paper. Preparation of academic texts in the formation of Regional Regulations is expected to improve the quality of Regional Regulations. For all parties, both formers of Regional Regulations, academics, and practitioners in compiling academic papers, it is hoped that they can pay attention to and meet the material and formal requirements in order to produce quality academic papers. At the level of implementation, there are still academic texts that have not met the formal and material requirements, among others, due to the preparation of academic papers after the Draft Regional Regulation has been drafted, inadequate time for preparing academic papers, improper use of budgets, the composition of the compilation team inadequate, as well as less supportive facilities and infrastructure. With regard to this urgency, the preparation of an academic text is mandatory in the preparation of Regional Regulations including the Draft Regional Budget Regional Regulations. The legal consequence is that if you do not prepare an academic paper in advance for the Regional Regulation, it will be null and void.